Limberg Flap is a Safe and Effective Procedure for the Surgical Treatment of Pilonidal Sinus in Sacrococcygeal Region - Islam, Md Rashidul; Matin, Abul Bashar Md Abdul; Ahmad, Sami; Islam, Md Armanul; Alam, Shoaeb Imtiaz (Journal of Shaheed Suhrawardy Medical College, 2021)
Pilonidal sinus in the sacrococcygeal region is an acquired condition and usually seen in young male adults. Diagnosis is indicated by to see the site and appearance of chronic discharging opening, and identification of midline pit in the natal cleft. The management of the sacrococcygeal pilonidal sinus varies from clipping of hairs with good hygiene of the area, wide excision of the area with primary or secondary closure and newer flap procedures, but none is widely accepted. The main concern for the treatment to the patient is the recurrence. This prospective study has been performed to determine the effectiveness and safety of the Limberg flap procedure for sacrococcygeal pilonidal sinus for new and recurrent cases. Primary end point was rate of recurrence and secondary end points were its complianceand complications such as wound infection, postoperative pain and return to work. A total of 17 patients were operated from March 2012 to June 2016.Both primary and recurrent diseases were included. All patients successfully underwent surgery. Patients complained very minimal postoperative pain. LO were average 2 days. All patients were discharged with negative suction drain in situ. Drains were removed on 7th POD and stitches were removed on 9th to 12th postoperative day. All patients returned to work after 2nd weeks. In our study no recurrence or major complications were found. Limberg flap for sacrococcygeal pilonidal sinus was found very useful and effective in terms of recurrence rate and patients morbidity. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 6-8